IMPROVING STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT BY USING IMAGE MEDIA - Khotimah, Husnul; Junaedi, Ahmad; Putri, Andi Mega Januarti (Universitas Khairun, 2024)
This research aims to find out whether writing descriptive text using image media can improve students' writing skill in English and To find out aspects that improved the most after the image was taught. The location of this research is in SMA Negeri 3 Majene. The approach used in this research is quantitative. The methodology of this research is a quasi-experimental design. The population consists of four classes with a total of 71 students of XI SMA Negeri 3 Majene. The sample of this study was two classes consisting of 20 students for the control group and 20 students for the experimental group. In the control group, the researcher used the conventional method and the experimental group used the descriptive text learning method using Picture Media. The treatment was carried out in 8 times per meeting. The researcher used an instrument, namely a writing test (pre- test and post-test). The student's pre-test means score is (50.50) and the students' post-test mean score is (70.00). Meanwhile, the independent sample t-test results show that Sig. (2-tailedÂ = 0.004) 0.05. That means learning with descriptive text using picture media can significantly improve students' writing skills.